STUDI EVALUASI PELAKSANAAN DAN DAMPAK PERATURAN DAERAH KOTA TANGERANG NOMOR 7 TAHUN 2005 TENTANG PELARANGAN, PENGEDARAN DAN PENJUALAN MINUMAN KERAS - Iwan, Iwan; Eliadi Hardian, Dafyar; Mulyadi, Edi (Perspektif : Jurnal Ilmu Administrasi, 2024)
This study uses a qualitative research approach where qualitative research as a scientific method is often used and implemented by a group of researchers. Qualitative research is conducted to build knowledge through understanding and discovery. The results of this study regarding the Evaluation of Regional Regulation Number 7 of 2005 concerning the Prohibition, Distribution and Sale of Alcoholic Beverages in Tangerang City can be said to have been running well but still not optimal. This is because there are still shortcomings in the implementation of the Tangerang City Prohibition, Distribution and Sale of Alcoholic Beverages policy in the policy input so that it affects the process of implementing the policy. The conclusions of this study are as follows: First, based on the input dimension, on the aspect of human resources in implementing the policy, Second, based on the process dimension, the mechanism for implementing this policy is quite clear, starting from raids, data collection of evidence, to action to sanctions given. can be said to be sufficient but still has some shortcomings, Third, based on the output dimension of implementation, the results of the implementation process of this policy itself are still not optimal in accordance with the objectives stated in the regional regulation itself, Fourth, based on the outcome dimension, the real impact caused by the implementation of the Prohibition, Distribution and Sale of alcoholic beverages can be seen that there are changes in people's lifestyle patterns. Keywords: Evaluation, Regional Regulation Number 7 of 2005, alcoholic beverages.